Sistem Sasi Soa dalam Pengelolaan Sumber daya Alam Pala di Negeri Seith Kecamatan Leihitu - Madani, Awangaditsya P; Pattiselanno, August E.; Kaplale, Raihana (Jurnal Agrosilvopasture-Tech, 2025)
Indonesia is widely recognized as an agrarian country, with a significant portion of its population engaged in agricultural activities. Statistical data from 2001 indicates that approximately 45% of Indonesians were employed in the agricultural sector. Among Indonesia’s native spice commodities, nutmeg holds a prominent position and contributes meaningfully to national development. One of the key nutmeg-producing regions is the village of Seith, located in the Leihitu sub-district, Central Maluku district, Maluku province. This community practices a traditional resource management system known as sasi soa, which governs the harvesting of nutmeg. This study aims to examine the existence, function, and impact of the sasi soa system, particularly its role in the sustainable management of nutmeg resources in Seith. The findings reveal that the sasi soa system is not only effective in regulating nutmeg harvesting but also contributes positively to the conservation of natural resources and the economic well-being of the local population. Notably, farmers who adhere to the sasi soa regulations report higher income levels compared to those who do not comply with the system. These results underscore the importance of integrating traditional ecological knowledge into contemporary resource management strategies.